Violence and melancholia: The story of melancholic “Butterfly” generation - Gündoğdu, Bucu (My University, 2016)
In his work entitled “Mercury fur”, Philip Ridley imagines a post–apocalyptic capitalist society plagued by the butterflies, multi-colored drugs, which induce memory loss and social collapse, particularly in younger generation. In addition to the drug dealing, violence and child abuse become another source of income in this capitalist world that suffers from loss of communication and empathy. This is one of the reasons that lead characters to develop melancholic subjectivity and strengthen their tendency to resort violence. Characters suffer from permanent melancholia state due to ongoing modern civil wars that turn the world into a “Waste Land” as in T.S Eliot’s poem. Just as Samuel Beckett’s characters, Vladimir and Estragon in “Waiting for Godot”, the brothers of “Mercury Fur”, Eliot and Darren think hope and belief are replaced with disbelief and despair. In this text, it is not an existential crisis that is focused on though, it is the post-war crisis causing moral bankruptcy and lack of commitment to life because threat is everywhere and capitalism demerits humane values. The Gang culture resurfaces again and dominates the young brains and incites them to do violent actions. This text has been examined from the perspective of Freudian theory of “Melancholia and Mourning”, which sheds light on the reasons why these characters suffer from melancholia, depressive psychoses and perversions. Though at first glance, it seems difficult to overcome shell-shock experience, moral degeneration and prevent familial institution’s disintegration, Ridley considers the best cure to work through the problems is story-telling. To exchange personal stories plays a big role in stimulating bitter-sweet memories, keeping family ties close and regaining sense of self even in the time of war.
Keywords: Philip Ridley; Mercury Fur; Violence and Melancholia; Story-telling